User Centric Media First International Conference, UCMedia 2009, Venice, Italy, December 9-11, 2009, Revised Selected Papers - Daras, Petros; Ibarra, Oscar Mayora; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference, UCMedia 2009, which was held on 9-11 December 2009 at Hotel Novotel Venezia Mestre Castellana in Venice, Italy. The conference`s focus was on forms and production, delivery, access, discovery and consumption of user centric media. After a thorough review process of the papers received, 23 were accepted from open call for the main conference and 20 papers for the workshops.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Information systems; Multimedia systems; Computer Science; Database Management; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Data Mining and Knowledge Discovery; User Interfaces and Human Computer Interaction; Multimedia Information Systems